2016
DOI: 10.18438/b8992d
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Student Demographics and Student Engagement with Online Library Instruction Modules

Abstract: Commons-Attribution-Noncommercial-Share Alike License 4.0 International (http://creativecommons.org/licenses/by-nc-sa/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. AbstractObjective -To investigate whether there are any demographic trends affecting student engagement with online library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…Meanwhile, in recent studies, demographic characteristics of students were examined in terms of their effect on e-learning activities, and the findings showed that age and grades of students significantly influence their SE and professional skills (e.g., Dahalan et al, 2012;Duan et al, 2018;Jung and Lee, 2018;Thill et al, 2016;Zhang and Liu, 2019). Lastly, students' demographic characteristics were also found to affect their APC and their accounting skill development (Anjum, 2020;Hassan et al, 2020;Helm, 2015;Kirstein et al, 2019;Szadziewska et al, 2017;Yanto et al, 2011).…”
Section: Student Demographics Moderates the Relationship Between Se A...mentioning
confidence: 99%
“…Meanwhile, in recent studies, demographic characteristics of students were examined in terms of their effect on e-learning activities, and the findings showed that age and grades of students significantly influence their SE and professional skills (e.g., Dahalan et al, 2012;Duan et al, 2018;Jung and Lee, 2018;Thill et al, 2016;Zhang and Liu, 2019). Lastly, students' demographic characteristics were also found to affect their APC and their accounting skill development (Anjum, 2020;Hassan et al, 2020;Helm, 2015;Kirstein et al, 2019;Szadziewska et al, 2017;Yanto et al, 2011).…”
Section: Student Demographics Moderates the Relationship Between Se A...mentioning
confidence: 99%
“…Lopatovska and Regalado [8] assessed students' behavior across four university libraries in New York City area and found that demographics, academic requirements, work habits and disciplinary affiliations accounted for the variations in their behavior towards library use. Investigating demographic trends influencing students' engagement in online library instruction, Thill, Rosenzweig and Wallis [9] established that age, academic performance, gender, race and ethnicity were significant factors. At the Pontificia Universidad Catolica de Chile, Jara, Clasing, Gonzalez, Montenegro, Kelly, Alaron, Sandoval and Saurina [10] indicated that library use by undergraduates varied across the various disciplines and level of study in the university.…”
Section: Literature Reviewmentioning
confidence: 99%
“…al, 2017, p. 182). Researchers also found that there are ties to online learning modules and research associated with demographics such as age and gender (Thill, Rosenzweig, and Wallis, 2016).…”
Section: Mobile Digital Access Design Use and Adoption In Librariesmentioning
confidence: 99%
“…are personally driven and motivated rather than supported by clearlyplanned, identified and integrated infrastructure across the institution" (Hinze et al, 2017, p. 182). Researchers also found that there are ties to online learning modules and research associated with demographics such as age and gender (Thill, Rosenzweig, and Wallis, 2016).…”
Section: Development Of Library Expertsmentioning
confidence: 99%